Mathematics for teachers : - Sonnabend, Thomas (Thomson Brooks/Cole, 2004)
This book provides guidance for elementary teachers who are looking to learn the basics of the varying levels of elementary math. Author provides an active, engaging approach to get students into the underlying concepts of elementary education mathematics. The book includes coverage of problem-solving, reasoning, sets, arithmetic, geometry, measurements, algebra, computers, statistics, and probability